1990
DOI: 10.1080/00150199008016513
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric ceramics with high coupling and high temperature stability

Abstract: A new method for making piezoelectric ceramics with high stability and high coupling is described. Two ceramics in the PZT system with compositions on opposite sides of the morphotropic phase boundary are prepared first. By means of mixed sintering. a mixture or composite ceramic is obtained. If the compositions of the two components and their weight ratio are carefully adjusted and the sintering temperatures are appropriate, the composite ceramic will possess very high temperature stability and a high couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The phase boundary between the tetragonal and the cubic occurs at x = 0.3 for the PAD films but at x = 0.4 for the PLD films. It is believed that the highest dielectric constant can be obtained at the phase boundary, as many other material systems [46,47]. The results demonstrated that the PAD technique has superior advantages in controlling the stoichiometry of complex dielectric oxide thin films and the dielectric properties of these films are comparable with the films grown by PLD.…”
Section: Controlling Ability On the Stoichiometrymentioning
confidence: 86%
See 1 more Smart Citation
“…The phase boundary between the tetragonal and the cubic occurs at x = 0.3 for the PAD films but at x = 0.4 for the PLD films. It is believed that the highest dielectric constant can be obtained at the phase boundary, as many other material systems [46,47]. The results demonstrated that the PAD technique has superior advantages in controlling the stoichiometry of complex dielectric oxide thin films and the dielectric properties of these films are comparable with the films grown by PLD.…”
Section: Controlling Ability On the Stoichiometrymentioning
confidence: 86%
“…The phase boundary between the tetragonal and the cubic occurs at x = 0.3 for the PAD films but at x = 0.4 for the PLD films. It is believed that the highest dielectric constant can be obtained at the phase boundary, as many other material systems [46, 47].…”
Section: Controlling Ability On the Stoichiometrymentioning
confidence: 99%
“…The relative content of low-spin Fe 2+ increased. The electron transportation of Fe 2+ ↔Fe 3+ can make the resistivity reduce to result in a certain amount of dielectric loss [13] .…”
Section: Xrd Analysismentioning
confidence: 99%
“…Solid State Phenomena Vols. 121-123 diversion polarization of equivalent dipole [12,13] . The contribution of every polarization mode is not same in different range of frequency.…”
Section: Dielectric Properties Of Lamno 3 Nanocrystalmentioning
confidence: 99%
“…Because of the steering diversion polarization of equivalent dipole, the virtual part (ε") of the complex permittivity (tg(δ)=ε"/ε') may has larger values to induce permittivity loss. The reasons of dielectric loss in hyperfrequency waves for nanosized LaMnO 3 was ordinary related to the characteristic effects of nanocrystalline [12] .Some special effects, such as quantum effect, small size effect and interface effect will appear when materials locate in nano-scale. These special effects lead to different microwave absorption properties for LaMnO 3 nanoparticles in electromagnetic field [14] .…”
Section: Dielectric Properties Of Lamno 3 Nanocrystalmentioning
confidence: 99%